Analysis of S gene characteristic sequences and changes in properties of protein expression in HBV ASCs with low-level HBsAg - Yu, Yu; Zhang, Yingqiang; Dai, Yuzhu; Sun, Qingyang; Jiang, Chun; Xu, Xujian; Mei, Chuanzhong; Cheng, Jun (Frontiers in Medicine, 2022)
Objective: We detected the serum HBsAg immune complex (HBsAg-CIC) and sequenced the HBV S gene in these patients to reveal the association between sustained low-level expression of HBsAg and mutated S gene sequence characteristics, protein function changes, and HBsAg immune complex formation. Methods: A total of 204 samples were collected and divided into high-level (n=60, HBsAg level >10 IU/ml) and low-level (n=144, HBsAg level ≤10 IU/ml) HBsAg groups. The clinical and epidemiological data of the two groups were statistically compared. According to different serological patterns and genotypes, the HBsAg-CIC results of the high-level and low-level HBsAg groups were divided into different subgroups, and then the HBsAg-CIC positive rates among different subgroups were compared. We sequenced the S gene of HBV from the two groups and identified the relevant mutations in the MHR of the S gene. In addition, we compared the changes in HBsAg protein properties and functions after hot spot mutation in the MHR of the S gene. Results: Comparing the positive rates of HBsAg-CIC under different serological patterns and genotypes in the two groups, the HBsAg-CIC positive rate was higher in the low-level HBsAg group. Moreover, there was weak correlation between HBsAg-CIC and HBsAg or HBV DNA in both groups (r=0.32,0.27, 0.41, 0.48; P<0.05). Sequencing of S gene in the two groups, showed that the hot-spot mutations were T126A, M133L/T/S and F134L/T/I in MHR of S gene of genotype B, and hot-spot mutations were Q101R and I126S/T in MHR of S gene of genotype C. Additionally, the positive rate of MHR mutation in the S gene from HBsAg-CIC positive patients was higher in the low-level HBsAg group. Conclusion: The host immune process of clearing HBV seems to have multiple site mutations in MHR, which changes the physicochemical properties and functions of HBsAg and intensifies the formation of HBsAg-CIC, thus avoiding the effective recognition of HBsAg by the host and resulting in immune tolerance between the host and HBV, which may be one of the formation mechanisms of sustained low-level expression of HBsAg in the serum of HBV-infected persons.